Al2O3/AlN/GaN MOS-Channel-HEMTs With an AlN Interfacial Layer - Liu, Shenghou; Yang, Shu; Tang, Zhikai; Jiang, Qimeng; Liu, Cheng; Wang, Maojun; Chen, Kevin J. (IEEE ELECTRON DEVICE LETTERS, 2014)
We report a high-performance normally-off Al2O3/AlN/GaN MOS-channel-high electron mobility transistor (MOSC-HEMT) featuring a monocrystalline AlN interfacial layer inserted between the amorphous Al2O3 gate dielectric and the GaN channel. The AlN interfacial layer effectively blocks oxygen from the GaN surface and prevents the formation of detrimental Ga-O bonds. Frequency-dispersion in C-V characteristics and threshold voltage hysteresis are effectively suppressed, owing to improved interface quality. The new MOSC-HEMTs exhibit a maximum drain current of 660 mA/mm, a field-effect mobility of 165 cm(2)/V . s, a high ON/OFF drain current ratio of similar to 10(10), and low dynamic ON-resistance degradation.